If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (19b + -3) + -9(2b + 1) = -7 Reorder the terms: (-3 + 19b) + -9(2b + 1) = -7 Remove parenthesis around (-3 + 19b) -3 + 19b + -9(2b + 1) = -7 Reorder the terms: -3 + 19b + -9(1 + 2b) = -7 -3 + 19b + (1 * -9 + 2b * -9) = -7 -3 + 19b + (-9 + -18b) = -7 Reorder the terms: -3 + -9 + 19b + -18b = -7 Combine like terms: -3 + -9 = -12 -12 + 19b + -18b = -7 Combine like terms: 19b + -18b = 1b -12 + 1b = -7 Solving -12 + 1b = -7 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 1b = -7 + 12 Combine like terms: -12 + 12 = 0 0 + 1b = -7 + 12 1b = -7 + 12 Combine like terms: -7 + 12 = 5 1b = 5 Divide each side by '1'. b = 5 Simplifying b = 5
| 8x+5=9x+18 | | 9w-5=2 | | 9x+4x+4+9=8x+3+4x | | 2x+7=5x+3 | | -5=-(x-3) | | 22=18-.4x | | -8y+2=-9y+1 | | F=3k+2w | | 3x+6=(x-5) | | 2x+(3y)= | | 8x-12=6x+6 | | 6x-4x+3=7+2x-1 | | -1(-36)=x | | 2(3x+9)=-12 | | -1(-36)= | | 8p+4=9+7p | | 22=3x-5 | | 3-7x+6x=4 | | -15+x=x+19 | | 9x^2-x+1=0 | | 4x-(3-x)+5=17 | | 14xy^2+2x^2y-6x^3y=0 | | -6x+2=3x+4 | | -25x-125=50 | | 6x-8x= | | 2x-8y=10 | | 6.1h=0.3-3.4h | | 4(8z+2)-3(8-z)= | | 12k^2-5k-2=0 | | 0.25x+0.5=0.25x-0.5 | | x^2+37=12x | | D(L-12n)=5L |